Pengurusan Surat Persetujuan Muat Barang Berbahaya di Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas I Dumai pada PT. Sinar Maritim Anugerah Cabang Dumai - Shella Apriyani Br Surbakti; Suparman Suparman; Aja Avriana Said (Jurnal Transformasi Bisnis Digital, 2024)
The purpose of this paper is to study the process of processing approval letters for loading dangerous goods and the obstacles at the Dumai Class I Harbormaster and Port Authority Office at PT. Sinar Maritim Anugerah Dumai Branch. In writing the paper the author used field observation methods (Field Research) and library methods (Library Research) related to the subject matter taken. In the ship agency, the company carries out activities to process permits for unloading dangerous goods. Processing the approval letter for loading dangerous goods goes through several stages starting from making an application letter for loading dangerous goods by the ship agent, paying Non-Tax State Revenue (PNBP) or PUP for one activity, completing the requirements attached to the application for permission to unload dangerous goods , permission to load dangerous goods from the loading port, B/L and manifest. Then hand it over to the administrative and administrative division for issuing permits for loading and unloading dangerous goods and then hand it over to the Head of Harbormaster and Port Authority (KSOP) for signing. The obstacles faced by companies in processing permits to load dangerous goods consist of obstacles from the company and at the harbormaster's office. On the other hand, in the process of processing permits to load dangerous goods, companies pay more attention to the accuracy of staff to avoid mistakes in completing the requirements for processing permits to load dangerous goods.